Brexit: A Long Way to Go - Mordecai, Aédán (2018)
Twelve months since Theresa May started the clock on the UK’s two-year journey towards exiting the EU, the transition arrangements and guidelines have been agreed. With a year to go, what are the potential stumbling blocks and how important will the Irish border be?